The Influence of Work Facilities and Individual Characteristics on Job Satisfaction (Pratama Karya Banaran Study) - Kristanti, Desi; Hariyanti, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to investigate how work facilities and individual characteristics impact job satisfaction at Pratama Karya Banaran. It employs explanatory research, which aims to uncover causal relationships between variables through hypothesis testing. The sample size consists of 40 individuals, selected using the Slovin formula from the entire employee population of Pratama Karya Banaran. The study utilizes data quality testing, classic hypothesis testing, and multiple linear regression as analytical tools. The results indicate that both work facilities and individual characteristics have a significant effect on job satisfaction. Moreover, the study highlights that working conditions, in conjunction with individual characteristics, collectively play a substantial role in determining levels of job satisfaction.